Training in de-escalation: an effective alternative to restrictive interventions in a secure service for women. (1st April 2016) - Long, Clive; Afford, Matthew; Harris, Rob; Dolley, Olga
The use of de-escalation in secure psychiatric settings is critical for preventing a cycle of escalation, restraint and seclusion. However, instruction in these skills is not always thorough or at an advanced level. This study describes a change in both the content and form of staff training in the prevention and management of violence in a women's secure psychiatric unit. A revised staff training programme with increased emphasis on prevention and de-escalation, on-ward training and the active involvement of patients in their risk management plans is described. A pre–post design compared risk behaviours, rates of seclusion and restraint, inpatient behaviour and staff views on the benefits of training in the year before and the year following change. Results show that an increase in on-ward training and more training time devoted to prevention and de-escalation was reflected in reductions in risk behaviours, seclusions, time spent in restraint and staff injuries. Staff rating of patient behaviour following change showed improvements in patient insight into risk, inappropriate behaviour, programme participation and relationships with staff. Findings are discussed in the context of study design limitations and on-going attempts to approximate best practice in secure settings for women.